ANALYSIS OF MANAGEMENT INFORMATION SYSTEMS SPARE PARTS G.A. SIWABESSY REACTOR – BRIDGE - Dwi Erny Erawati; Sunarto Usna, Drs, MMSI (Jurnal Sistem Informasi, 2002)
Computerization as one of solving a problem that is very helpful in data processing so it can produce the information quickly, accurate and relevant if the lawyer-entry of data was performed every time the activities are done. Use of computer equipment will affect the presentation of information at any time if necessary needed will be easy to obtain and ensure keama devoted to him. On the system proposed no changes to the system, only the lawyer-entry of data that occurs done once a week, now conducted every time there is activity data entry and data out.